T-scan II occlusal analysis in restorative dentistry - Lazić Vojkan; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2002)
The comparison of accufilm markings and computerized T-Scan II force plots of restorations and occlusal interferences in intercuspal position of the lower jaw, before and after occlusal adjustment showed a great improvement in force distribution, balance of occlusal forces and evenness of the right and left side. The computer analysis through T-Scan II system help us to clearly understand what those well balanced occlusal contacts and force distribution really mean for the proper restorative occlusal therapy.